Foreigners’ Understanding of Culture in Indonesia: A Qualitative Interview Study - Suhaila, Izzati; Sitompul, Rizki Nurhidayah; Harahap, Fitri Ramadani (Journal of Applied Linguistics, 2025)
This study examines the perspective of foreign citizens toward Indonesia through qualitative interviews conducted with lecturers, students, and tourist. It analyzes aspect of cultural interaction, hospitality, and interfaith perceptions. The findingsreveal a dynamic blend of appreciation, cultural exchange and occasional misperceptions, all of which contribute to a richly nuanced image of Indonesia within the Global comunnity. The study also emphasizes the importance of personal interactions in shaping foreigners’ perceptions of Indonesia identity. Fieldwork was carried out directly by lecturers and students through case studies involving English-language interviews with International Visitors in Medan. A mixed-method approach with a descriptive framework was used. The results show that foreign cultural representation at Maimun Palace in Medan reflects various aspects of personal tourism, particularly visitors’ interest in exploring local culture at the historical site. Keywords : Culture, Foreign, Language